Targeting the protein prenyltransferases efficiently reduces tumor development in mice with K-RAS-induced lung cancer - Liu, Meng (National Academy of Sciences, 2010)
RAS and RHO proteins, which contribute to tumorigenesis and metastasis, undergo posttranslational modification with an isoprenyl lipid by protein farnesyltransferase (FTase) or protein geranylgeranyltransferase-I (GGTase-I). Inhibitors of FTase and GGTase-I were developed to block RAS-induced malignancies, but their utility has been difficult to evaluate because of off-target effects, drug resistance, and toxicity. Moreover, the impact of FTase deficiency and combined FTase/GGTase-I deficiency has not been evaluated with genetic approaches. We found that inactivation of FTase eliminated farnesylation of HDJ2 and H-RAS, prevented H-RAS targeting to the plasma membrane, and blocked proliferation of primary and K-RAS(G12D)-expressing fibroblasts. FTase inactivation in mice with K-RAS-induced lung cancer reduced tumor growth and improved survival, similar to results obtained previously with inactivation of GGTase-I. Simultaneous inactivation of FTase and GGTase-I markedly reduced lung tumors and improved survival without apparent pulmonary toxicity. These data shed light on the biochemical and therapeutic importance of FTase and suggest that simultaneous inhibition of FTase and GGTase-I could be useful in cancer therapeutics.